2016
DOI: 10.1038/srep35582
|View full text |Cite
|
Sign up to set email alerts
|

Spin pumping in magnetic trilayer structures with an MgO barrier

Abstract: We present a study of the interaction mechanisms in magnetic trilayer structures with an MgO barrier grown by molecular beam epitaxy. The interlayer exchange coupling, Aex, is determined using SQUID magnetometry and ferromagnetic resonance (FMR), displaying an unexpected oscillatory behaviour as the thickness, tMgO, is increased from 1 to 4 nm. Transmission electron microscopy confirms the continuity and quality of the tunnelling barrier, eliminating the prospect of exchange arising from direct contact between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
18
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 27 publications
5
18
2
Order By: Relevance
“…The possibility of an enhancement of the indirect exchange via a resonant coupling between localized states and a FM contact has been already addressed for the issues of magnetic exchange [ 48 ,, 49 ] and spin-pumping effect between a FM insulator and a non-magnetic metal [50,51] . The scenario (iv) is also supported by the recent observations of the existence of an interlayer exchange coupling in relatively thick FM/MgO/FM junctions (1-3nm) revealed by a minimum value around 2nm [52] . This conclusion is reinforced by our results in the MgO thickness series samples showing up an increase of the ISHE signal with larger MgO barriers.…”
Section: Evidence Of Spin Pumping In Localized States At Mgo/si Intersupporting
confidence: 74%
“…The possibility of an enhancement of the indirect exchange via a resonant coupling between localized states and a FM contact has been already addressed for the issues of magnetic exchange [ 48 ,, 49 ] and spin-pumping effect between a FM insulator and a non-magnetic metal [50,51] . The scenario (iv) is also supported by the recent observations of the existence of an interlayer exchange coupling in relatively thick FM/MgO/FM junctions (1-3nm) revealed by a minimum value around 2nm [52] . This conclusion is reinforced by our results in the MgO thickness series samples showing up an increase of the ISHE signal with larger MgO barriers.…”
Section: Evidence Of Spin Pumping In Localized States At Mgo/si Intersupporting
confidence: 74%
“…Moreover, the presence of oxygen through iron oxide electrodes [11,25] or interface oxidation [12,18] influences bilinear and/or biquadratic coupling. We point out that a weaker ferromagnetic coupling (<0.03 erg/cm 2 ) has also been * christine.bellouard@univ-lorraine.fr reported for MgO thicknesses close to 1 nm [9,10,24]. In the case of sputtered junctions, a ferromagnetic coupling has been observed in the planar magnetic configuration with an exponential MgO thickness dependence [13,17], and has therefore been attributed to a cooperative electronic effect.…”
Section: Introductionmentioning
confidence: 82%
“…On the contrary, for a semiconducting or insulating spacer [3][4][5][6][7][8], magnetic properties seem to depend deeply on growth conditions and then on structural specifications. Among them, the MgO spacer [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] appears unique in presenting a large variety of experimental results. They concern either the MgO thickness range and the coupling sign and strength, or the junction magnetic geometry (planar or perpendicular magnetization).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of both Si and oxide semiconductors 13 , have also shown some suppression of spin pumping and suggest that the carriers may continue to allow spin diffusion through the barrier. Baker et al 14 15 reported a rapid decrease in the damping due to reduced spin pumping with the addition of an ultra-thin MgO barrier layer between Fe and Pt, from which it was concluded that spin current can tunnel through a few monolayers of an insulating oxide barrier. The work was supported by transmission electron microscopy (TEM) imaging, which is limited to sampling very small areas and provides a projection of a thin 3D sample volume that may not show pinhole defects, and any defects present may be difficult to directly image 16 .…”
mentioning
confidence: 99%